Rapid weight loss and combat athletes: a study on psychological resilience and mechanical hyperalgesia - Çağlar, Esin Çağla; Ceylan, Levent; Ağralı Ermiş, Sermin; Çamiçi, Furkan; Eliöz, Murat; Uzun, Recep Nur; Çiçek, Güner; Kusan, Muhammet; Bayraktar, Mustafa Tolga; Şahin, Fatma Neşe; Küçük, Hamza (Frontiers in Psychology, 2025)
IntroductionThe study investigates the effects of Rapid Weight Loss (RWL) on the levels of psychological resilience and mechanical pain sensitivity in elite kickboxers. The primary aim was to examine changes in psychological resilience subdimensions and pressure pain threshold (PPT) values in the thoracolumbar region before and after a one-month RWL period leading up to competition. Hypotheses included expectations of significant reductions in PPT values due to biomechanical and physiological changes during RWL, along with improvements in psychological resilience subdimensions due to structured routines and social support.MethodsThirty-seven elite male athletes (age: 22.94 ± 1.98) participated in the study. Psychological resilience was assessed using the Psychological Resilience Scale for Adults, and mechanical pain sensitivity was evaluated through Pressure Pain Threshold (PPT) measurements. Measurements were conducted before and after the RWL period, spanning one month prior to competition.ResultsThe results revealed significant PPT values across all thoracolumbar segments after RWL (p < 0.001). Cohen’s d values indicated large effect sizes for these changes (d = 2.10–2.36). The L5 segment exhibited the largest PPT decrease (t = −10.45, d = 2.36), while the Th1 segment showed the smallest decrease (t = −8.23, d = 2.10). Measurements taken at 4 cm from the spine midline also demonstrated significant PPT reductions (p < 0.001), with the highest change recorded in the L5 segment (t = −9.78, d = 2.30). Psychological resilience subdimensions, including “structured style,” “social competence,” “future orientation,” and “social resources,” improved significantly after RWL (p < 0.05), while “family cohesion” and “personal strength” did not show significant changes. Athletes who previously ranked in tournaments exhibited higher psychological resilience, potentially due to enhanced self-confidence.DiscussionThese findings align with literature suggesting that competitive success and optimism play crucial roles in resilience development. Personality traits and perceived social support further contributed to the observed resilience levels. This study highlights the multidimensional impact of RWL, emphasizing its detrimental effects on pain sensitivity and its mixed outcomes on psychological resilience. RWL-associated increases in mechanical hyperalgesia, especially in the lumbar region, were attributed to biomechanical and neurophysiological factors. Enhanced psychological resilience observed in certain subdimensions underscores the importance of structured and social support systems in mitigating RWL-induced stress. Future research should explore interventions to optimize resilience and manage pain during RWL periods, focusing on individualized support strategies for athletes. These findings contribute to understanding the interplay between psychological and physiological factors during RWL, practical insights for athletic training.